PENGHAMBATAN AKTIVITAS α-GLUKOSIDASE DARI EKSTRAK METANOL BUNGA BUGENVIL (Bougainvillea glabra Choisy) - Puspitasari, Intan Dessy; Saleh, Chairul; Hairani, Rita; Ruga, Ritbey (JURNAL ATOMIK, 2024)
The test of Phytochemical screening and antidiabetic activity of methanol extract of bugenvil (Bougainvillea glabra Choisy) flower against α-glucosidase inhibition have been conducted. This study aims to determine the content of secondary metabolite compounds and the effectiveness of the methanol extract of bugenvil flower against α-glucosidase activity. Phytochemical test showed that the methanol extract contained secondary metabolite compounds namely alkaloids, flavonoids, steroids, phenolics and saponins. By 50 µg/mL, the methanol extract of bugenvil flower can inhibit α-glucosidase activity with a percent inhibition value of 79.42% while acarbose as a positive control in this study exhibited antidiabetic activity against α-glucosidase of 99.30% at a concentration of 0.00006 µg/mL.